1995
DOI: 10.1126/science.7638620
|View full text |Cite
|
Sign up to set email alerts
|

Association of Flavin Adenine Dinucleotide with the Arabidopsis Blue Light Receptor CRY1

Abstract: The arabidopsis thaliana HY4 gene encodes CRY1, a 75-kilodalton flavoprotein mediating blue light-dependent regulation of seedling development. CRY1 is demonstrated here to noncovalently bind stoichiometric amounts of flavin adenine dinucleotide (FAD). The redox properties of FAD bound by CRY1 include an unexpected stability of the neutral radical flavosemiquinone (FADH.). The absorption properties of this flavosemiquinone provide a likely explanation for the additional sensitivity exhibited by CRY1-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
385
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 410 publications
(406 citation statements)
references
References 22 publications
19
385
1
1
Order By: Relevance
“…Because of the high sequence and structural similarities between photolyase and CRY, it is generally assumed that CRYs have the same two cofactors as well. However, no CRY has been purified to date from its native source and those that have been purified as recombinant proteins contain FAD to varying levels and either trace amounts of MTHF or none at all (Lin et al 1995;Malhotra et al 1995;Özgür and Sancar 2003;Song et al 2007). Hence, formal proof that CRYs contain MTHF, or any other secondary chromophore, is lacking.…”
Section: Structures Of Photolyase and Cryptochromementioning
confidence: 99%
See 2 more Smart Citations
“…Because of the high sequence and structural similarities between photolyase and CRY, it is generally assumed that CRYs have the same two cofactors as well. However, no CRY has been purified to date from its native source and those that have been purified as recombinant proteins contain FAD to varying levels and either trace amounts of MTHF or none at all (Lin et al 1995;Malhotra et al 1995;Özgür and Sancar 2003;Song et al 2007). Hence, formal proof that CRYs contain MTHF, or any other secondary chromophore, is lacking.…”
Section: Structures Of Photolyase and Cryptochromementioning
confidence: 99%
“…Human cells expressing both genes and recombinant proteins encoded by both genes were tested for CPD and (6-4) photolyase activities and were found to lack both. Moreover, the proteins encoded by these genes, like most photolyases (Johnson et al 1988) and Arabidopsis CRY (Lin et al 1995;Malhorta et al 1995), contained FAD (flavin-adenine dinucleotide) and a pterin cofactor. Therefore, it was concluded that these proteins were not repair enzymes but that, like Arabidopsis CRYs, they performed non-repair-related blue light functions and were named human CRY1 and 2 (Hsu et al 1996).…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…As is the case for phototropism in Arabidopsis, suppression of hypocotyl elongation in this species shows some sensitivity in the green. In this latter case, the most likely explanation is that the FAD in CRYl © 1997 Blackwell Science Ltd, Plant, Cell and Environment, 20, 768-772 can exist stably in a semiquinone form (Lin et al 1995b), a moiety with significant absoiption in the green portion of the visible spectrum. Since the evidence cited above supports the hypothesis that the photoreceptor for phototropism is a dual chromophore protein, the model seems reasonable.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Ahmad & Cashmore (1993) described the isolation and characterization of an Arabidopsis gene, HY4, that probably encoded the photoreceptor for blue light-induced suppression of hypocotyl elongation. Subsequent biochemical studies (Lin et al 1995b) and investigations with transgenie plants overexpressing the HY4 gene product CRYl (Lin etal. 1995a) have confirmed this conclusion.…”
Section: Enter Arabidopsismentioning
confidence: 99%